STATE, LEGITIMATE VIOLENCE AND ACTIVITIES OF PRIVATE MILITARY-SECURITY COMPANIES IN THE MODERN WORLD - D. O. Novikova (Сравнительная политика)
State, legitimate violence and activities of private military-security companies in the modern world.